Negotiating Scientific Identity and Agency: Graduate Student Perspectives on a Public Communication of Science Course - Lilly Campbell (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
Drawing on interviews with nine graduate science students, this article explores perspectives on a Public Communication of Science (PCS) course designed to help students translate their research for a public talk given at a local town hall. I first outline the history of the student-run course and then discuss three course components—public rhetoric of science; improvisation; and audience awareness. Within each component, I describe one student’s particular experience with the course. I describe how students transferred rhetorical lessons from the course to their academic writing but could also transfer rigid views of communication from their scientific work back into their public talks. I also argue that the PCS course helped students to embody flexible scientific identities, but also had the potential to alienate them from norms of communication in their field. Meanwhile, their strategies for imagining and speaking to the public remained constrained by limited access to a range of audience perspectives. Findings demonstrate that there is much to be gained in challenging science students to translate their findings for new audiences. At the same time, instructors must continue to think critically about how we can help students to imagine and access a range of publics.